Students’ preferences on the design of electronic teaching presentation and their learning style - Lim, Siew Huang (2008)
The purpose of this research is to find out the most annoying about electronic teaching presentation specifically for delivery techniques and visual design among the final year students. The researcher investigated the final year students’ preferences on the visual design of electronic teaching presentation. In addition, the researcher identified the students’ preferences learning style, in order to determine whether there is any relationship between final year students’ learning style and their preferences on the visual design of electronic teaching presentation. There are 150 respondents among the final year students from SPI, SPK, SPL, SPP, SPS, and SPT of Faculty of Education, Universiti Teknologi Malaysia. The learning style model used in this research was Kolb’s Learning Style Inventory. A set of questionnaire used as the research instrument consisted of 56 items. There were four sections in the questionnaire. The reliability of research instrument had been determined through a pilot study with the alpha value 0.719 for Section C and 0.754 for Section D. The data had been analysed descriptively by using Statistical Package for the Social Science (SPSS) version 13 for Windows software and had been presented in the form of percentage, mean or Eta value. The findings showed the most annoying about electronic teaching presentation on the visual design was the text small in size which cannot be read (28.7%) and on delivery method was the instructors read the slide to the students (21.3%). Besides that, students preferred image background, image or picture as the main element to deliver the content of presentation, san-serif font type, and the title to be always on top of the slides than at the bottom. The students’ learning style preferred was feeler (converger) with 32%. Finally, there was a weak relationship between the final year students’ learning style and their preferences on the visual design of electronic teaching presentation with Eta value 0.166.